Manuel Sobrinho Rodrigues Simões: o percurso do Médico, Investigador e Professor - Maria Inês Neves Cunha (2022)
Manuel Sobrinho Rodrigues Simões (1918-1989) was a Doctor, graduated from the Faculty of Medicine of University of Porto, and a Full Professor of Physiological Chemistry of the same faculty. He graduated with the final grade of 18, the best student of the course. With the same grade he completed his PhD in Medicine and Surgery, with the dissertation "On lipid mobilization in alloxan diabetes" (1951). In 1956-57 he attended the Department of Biochemistry at the University of Oxford, where he worked with Hans Krebs, Nobel Prize for Medicine (1953) and, in 1965, he published one of the most cited articles of Portuguese medical literature. He was an excellent Doctor and Researcher, an exemplary Professor and an exceptional Man.